A study on anode diffusion layer for performance enhancement of a direct methanol fuel cell. (15th October 2016) - Liu, Guicheng; Li, Xinyang; Wang, Meng; Wang, Manxiang; Kim, Ji Young; Woo, Jae Young; Wang, Xindong; Lee, Joong Kee
Highlights: Wettability and morphology of diffusion layer were investigated. Surface modifications of sintering and Nafion treatment were discussed. Anode diffusion layer was optimized to adapt to high discharge current. Abstract: To optimize mass transfer property and electronic conductivity for direct methanol fuel cells with high discharge current density, in this paper, the influence of the modified components in anode diffusion layer on fuel cell performance has been investigated systematically. The modifications include binder type, carbon powder loading and sintering treatment in microporous layer, and surficial decoration of supporting layer. The fuel cell based on the hydrophilic diffusion layer which consisted of the microporous layer with Nafion binder and the supporting layer modified by Nafion emulsion, has shown the highest performance of 272.6 mW cm −2 at 80 °C and 0.3 MPa oxygen. The results indicate that the Nafion binder and sintering treatment are favorable for improving transfer properties of methanol solution and electron in anode microporous layer. The optimal carbon powder loading, 1.0 mg cm −2, balances the conflict between mass transfer property and the contact area of the supporting and catalyst layers. The order mass transfer is also realized by the surficial decoration with 5 wt.% of Nafion in supporting layer. In short, the hydrophilic anode diffusion layer is suitable for the fuel cell with high performance.